Examining the President's 2024 Election Strategy through Weberian Conflict Theory - Holqi, Fikri Gali Fernando; Zulfa, Arinda Maulidya (FISIP UIN SGD Bandung, 2024)
As Head of State, a President has a very vital role in efforts to maintain state sovereignty. However, in the 2024 general election in Indonesia, the President reaped negative sentiments identified as the term